Wind power as an alternative to sustain the energy needs in Garoua and Guider, North Region of Cameroon - Vincent Godwe Gormo (Elsevier, 2021)
The North Region of Cameroon is home to a 72 MW hydroelectric dam, which provides electricity beyond the region’s needs. However, aging dam and distribution network leading to frequent load shedding, are contributing factors to look for other environmentally friendly alternatives such as wind power to sustain the energy needs of the region. Wind energy can significantly contribute to the energy mix, mainly during the dry season (March, April and May) when energy demands highly rise and load shedding can last forever, mainly in rural or remotes locations. The main purpose this study to evaluate the wind energy production, using bihourly data collected at 10 m above ground level over a period of fifteen years from 2005 to 2019 for the localities, Garoua and Guider. The novelty of this study is 2D and 3D topographical maps of the wind resource of Garoua and Guider have been computed as well as the map of wind energy produced using the WAsP software, with an accurate determination of wind speed, wind power density and energy produced. Based on the results, wind power can be considered as a reliable alternative for renewable energy production, if optimal site selection is made.